2011
DOI: 10.1371/journal.pone.0018804
|View full text |Cite
|
Sign up to set email alerts
|

Incongruence in Doping Related Attitudes, Beliefs and Opinions in the Context of Discordant Behavioural Data: In Which Measure Do We Trust?

Abstract: BackgroundSocial psychology research on doping and outcome based evaluation of primary anti-doping prevention and intervention programmes have been dominated by self-reports. Having confidence in the validity and reliability of such data is vital.Methodology/Principal FindingsThe sample of 82 athletes from 30 sports (52.4% female, mean age: 21.48±2.86 years) was split into quasi-experimental groups based on i) self-admitted previous experience with prohibited performance enhancing drugs (PED) and ii) the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 38 publications
2
36
1
2
Order By: Relevance
“…[13] However, RRT has limitations. [1,14,23,24] Therefore, Lentillon-Kaestner and Ohl [1] suggest not to use one way of questioning to evaluate doping prevalence. [22] Therefore, it is necessary to collect larger samples than for the direct question method.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] However, RRT has limitations. [1,14,23,24] Therefore, Lentillon-Kaestner and Ohl [1] suggest not to use one way of questioning to evaluate doping prevalence. [22] Therefore, it is necessary to collect larger samples than for the direct question method.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[13] Although studies have shown that RRT limits the influence of social desirability, its complexity and unfamiliarity for respondents could also lead to careful and not necessarily honest answers. [1,14,23,24] Therefore, Lentillon-Kaestner and Ohl [1] suggest not to use one way of questioning to evaluate doping prevalence. Data based on a combination of available techniques (i.e.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This approach has been successfully employed in research investigating social cognitive factors in prohibited performance enhancing and illicit drug use [7,8]. …”
Section: Methodsmentioning
confidence: 99%
“…Anti-doping efforts should aim to target modifiable factors, such as the environment and determinants of athletes' thinking process, that in a favourable context could lead to doping use. Based on published research to date, this latter group includes, but is not limited to, outcome expectancies (Petroczi and Aidman 2008), social projection (Petróczi et al 2008c, Petroczi et al 2010b, Uvacsek et al 2011, mental mapping of doping (Petróczi et al 2010c), susceptibility (Gucciardi et al 2010), risk-taking propensity (Petroczi and Aidman 2008), moral values (Strelan and Boeckmann 2006) and shame (Bloodworth and McNamee 2010). Changing beliefs and expectations via providing acceptable alternatives to doping may also offer a feasible approach utilized in anti-doping (James et al 2010), so do timing and targeted interventions focusing on critical periods such as career transition stages or recovery from injuries (Petroczi and Aidman 2008, Lentillon-Kaestner and Brissonneau 2009.…”
Section: Assessing Contributing Factors: Understanding Doping Behaviourmentioning
confidence: 99%